2015
DOI: 10.1371/journal.pone.0127112
|View full text |Cite
|
Sign up to set email alerts
|

C-Peptide Is Independently Associated with an Increased Risk of Coronary Artery Disease in T2DM Subjects: A Cross-Sectional Study

Abstract: ObjectiveC-peptide has been reported to be a marker of subclinical atherosclerosis in type 2 diabetes mellitus (T2DM) patients, whereas its role in coronary artery disease (CAD) has not been clarified, especially in diabetics with differing body mass indices (BMIs).Design and MethodsThis cross-sectional study included 501 patients with T2DM. First, all subjects were divided into the following two groups: CAD and non-CAD. Then, binary logistic regression was used to determine the risk factors for CAD for all pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 35 publications
3
20
0
Order By: Relevance
“…It could be used to represent endogenous insulin secretion by islet β cells and insulin resistance . Studies have found that C‐peptide is significantly associated with NAFLD, being one of the three most important predictors in the general US population, as well as potential risk factors and outcomes of NAFLD, such as cardiovascular diseases and MetS . However, rather limited studies have measured the association between C‐peptide and advanced NAFLD stages.…”
Section: Introductionmentioning
confidence: 99%
“…It could be used to represent endogenous insulin secretion by islet β cells and insulin resistance . Studies have found that C‐peptide is significantly associated with NAFLD, being one of the three most important predictors in the general US population, as well as potential risk factors and outcomes of NAFLD, such as cardiovascular diseases and MetS . However, rather limited studies have measured the association between C‐peptide and advanced NAFLD stages.…”
Section: Introductionmentioning
confidence: 99%
“…According to Wang et al (2015) [28], a fasting C-peptide level greater than 1 ng/dl in a patient who has had diabetes for more than 1-2 years is suggestive of T2DM (i.e. residual b-cell function).…”
Section: Discussionmentioning
confidence: 99%
“…93 However, patients with early T2DM and insulin resistance have elevated serum levels of C-peptide, and an increased cardiovascular risk has been reported in these patients. 94 In addition, several studies in individuals without diabetes showed positive correlation between Cpeptide levels and the incidence of several cardiovascular diseases, such as coronary artery disease and myocardial infarction. [95][96][97] Altogether, these data suggest that elevated C-peptide levels, due to insulin resistance, contribute to atherosclerosis vascular disease in these patients.…”
Section: Figurementioning
confidence: 99%